The Influence Of Attitude, Motivation, Personality On Students' Entrepreneurial Interests Through The Family Environment As A Mediation Variable On Students Of The Management Study Program, Makassar State University - Sumiharja Darmawinata, Widhi Nugraha; Syamsul Rijal; Muhammad Ma'ruf Idris (SEAN Institute, 2024)
This study aims to determine how much influence attitudes, motivation, and personality have on entrepreneurial interest through the family environment as a mediating variable in Management Study Program students at Makassar State University, both direct influence and indirect influence. The research method used in this study is a quantitative method with Structural Equation Modeling (SEM) analysis using a questionnaire as a research instrument, and the analytical tool used is SmartPLS version 3.0. From the results of this study it was found that attitude has a positive but insignificant effect on entrepreneurial interest, motivation has a positive and significant effect on entrepreneurial interest, personality has a negative and insignificant effect on entrepreneurial interest. Furthermore, attitude and personality have a positive but insignificant effect on family environment, motivation has a negative and insignificant effect on family environment, family environment has a positive and significant effect on entrepreneurial interest. Attitude and personality have a positive but insignificant effect on entrepreneurial interest through the family environment, Motivation has a negative and insignificant effect on entrepreneurial interest through the family environment.